2013
DOI: 10.3906/bot-1302-49
|View full text |Cite
|
Sign up to set email alerts
|

Shortcut to long-distance developing of a tissue culture medium: micropropagation of mature almond cultivars as a case study

Abstract: IntroductionEvidently the development and the use of a defined tissue culture medium are among the most important factors that affect explant morphogenic reactions and the success of in vitro studies. The growth of cultures (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
0
11
0
6
Order By: Relevance
“…The wide application of MS, WPM, and QL media as standard growth media for all Prunus rootstocks, for the purpose of micropropagation and as a source of leaf explants for transformation and regeneration, has given the false impression that these rootstocks would be difficult to culture if they do not grow well on MS, WPM, and QL media. Previous studies with diverse Prunus genotypes confirmed that the so-called standard media require an optimization of nutrients for the successful micropropagation of the unique rootstock or cultivar of Prunus (Nas et al, 2013; Nezami Alanagh et al, 2014). Our initial studies showed that the NH 4 NO3- and KNO3+ components of the MS medium were inadequate for optimal growth and multiplication of G × N15 rootstock (Arab et al, unpublished data).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The wide application of MS, WPM, and QL media as standard growth media for all Prunus rootstocks, for the purpose of micropropagation and as a source of leaf explants for transformation and regeneration, has given the false impression that these rootstocks would be difficult to culture if they do not grow well on MS, WPM, and QL media. Previous studies with diverse Prunus genotypes confirmed that the so-called standard media require an optimization of nutrients for the successful micropropagation of the unique rootstock or cultivar of Prunus (Nas et al, 2013; Nezami Alanagh et al, 2014). Our initial studies showed that the NH 4 NO3- and KNO3+ components of the MS medium were inadequate for optimal growth and multiplication of G × N15 rootstock (Arab et al, unpublished data).…”
Section: Discussionmentioning
confidence: 93%
“…The majority of Prunus micropropagation studies of Prunus rootstocks have used a single mineral nutrient formulation to determine the effects of various PGRs (Andreu and Marín, 2005; Ruzic and Vujovic, 2008). Unfortunately, because of the complexity of interactions between medium constituents, it is very difficult to determine the optimum levels of minerals and organic compounds for a culture medium (Nas et al, 2013). The wide application of MS, WPM, and QL media as standard growth media for all Prunus rootstocks, for the purpose of micropropagation and as a source of leaf explants for transformation and regeneration, has given the false impression that these rootstocks would be difficult to culture if they do not grow well on MS, WPM, and QL media.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations